2017
DOI: 10.1016/j.jorganchem.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Some insights into the gold-catalysed A 3 -coupling reaction

Abstract: Abstract.A series of cyclometallated and functionalised NHC gold(I) and gold(III) complexes, many of which feature chiral ligands, and their application to A 3 -coupling reactions is presented. Gold(III) complexes were found to be particularly effective catalysts for the coupling in a range of solvents, however no asymmetric induction was obtained when using chiral gold complexes and the rate of product formation was found to be similar even when using different ligand systems. In-situ NMR analysis of these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…Given the beneficial effects that we[7a] and others[11e], [11g] have noted in the promotion of A 3 ‐reactions when using focused microwave radiation as a heating source we turned our attention to this mode of activation in the present study. After some experimentation we noted that much reduced reaction times (30 min instead of 16 h) and catalyst loadings (typically 2 mol‐%) can be utilised to good effect when irradiating these reactions (to an internal temperature of 150 °C) in a focused microwave reactor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the beneficial effects that we[7a] and others[11e], [11g] have noted in the promotion of A 3 ‐reactions when using focused microwave radiation as a heating source we turned our attention to this mode of activation in the present study. After some experimentation we noted that much reduced reaction times (30 min instead of 16 h) and catalyst loadings (typically 2 mol‐%) can be utilised to good effect when irradiating these reactions (to an internal temperature of 150 °C) in a focused microwave reactor.…”
Section: Resultsmentioning
confidence: 99%
“…The complexes 3a , 4a and 4b have been characterised by single‐crystal X‐ray crystallography where it has been shown that, in the case of 3a and 4a , the ligand binds to Ag + in both endo ‐ and exo ‐modes generating one‐dimensional co‐ordination polymers , . A 3 ‐reactions proceed efficiently in either toluene or aqueous media when conducted in the presence of these complexes; A 3 ‐coupling reactions conducted in a focused microwave[11e], [11g], [7b], reactor have a beneficial effect both on reaction rate and catalyst loading. Further optimisation of these A 3 ‐reactions is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient catalysts based on N‐heterocyclic carbene complexes of coinage metals have been developed during past few years. [ 28–37 ] Copper‐based catalysts because of natural abundance of copper metal and high reactivity have also attracted great attention. [ 38 ]…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous catalysts based on a large number of transition metal ions have been used for the A 3 coupling reaction, including Cu [ 8 , 9 , 10 , 11 , 12 ], Ag [ 13 , 14 , 15 , 16 ], Cu/Ru bimetallic systems [ 17 , 18 ], Zn [ 19 , 20 , 21 ], Fe [ 22 , 23 ], In [ 24 , 25 ], Ir [ 26 , 27 ], Hg [ 28 ], Ni [ 29 ], Rh [ 30 ], Mn [ 31 ], Co [ 32 ], Bi [ 33 ], and Cd [ 34 ]. Over the past few years, increasing attention has been paid to the catalytic performance of Au in promoting the A 3 coupling reaction, including Au(I) and Au(III) salts and organic Au complexes [ 35 , 36 , 37 , 38 ]. Despite cationic Au species showing very high catalytic activity, their rapid reduction under alkyne activation conditions is an important drawback [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%